Psychological Effects of Sedentary Behaviour Among Medical Students - Syed Ahmed Mahmud, Muhammad Amin Khan, Naeem Amjad, Farrukh Sarrfraz, Qurratulain Mehfooz, Muhammad Saifullah (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Physical and sedentary activities have been distinguished as possibly modifiable hazard components for many diseases, counting mental ailment, and may be effective targets for open health policy and intervention. However, the relative commitment of physical activity versus sedentary conduct to mental wellbeing is less clear. Objective: To identify the psychological effects of sedentary behaviour among medical students Study Design: Quantitative cross sectional Settings: M Islam Medical College Gujranwala Duration: Three months i.e. 1st January 2022 to 30th March 2022 Data Collection procedure: The study was conducted at M Islam Medical College Gujranwala to identify the psychological effects of sedentary behaviour among medical students. The cross sectional study conducted over 200 medical students. The Korean form of the Perceived Stress Scale (PSS), which was developed by Cohen et-al, was utilized in this study. Anxiety was measured with the Beck Anxiety Inventory (BAI), a self report scale that was created by Beck et al. Depression was measured utilizing the Center for Epidemiological Studies-Depression Scale (CES-D). Results: The total number of students who were participated in the study was 200 in which 82 were males and 118 were females. Psychological effects of sedentary behaviour among medical students on hourly basis, week days and on weekends were calculated. BMI, Mean and standard deviation were calculated in regard to stress, anxiety and depression. Practical implication Conclusion: Stress, anxiety, and depression are genuine mental wellbeing issues among college student groups. The sedentary behavior of college students was found to be significantly related to their mental problems in the present study. Be that as it may, until now, research has rarely been conducted to identify the mechanisms or interceding variables that clarify the relationship between sedentary behavior and stress, anxiety, and depression. Keywords: Sedentary behaviour, stress, psychological, anxiety, depression